The Influence of Corruption on Management in Modern Russia - Moiseev, Vladimir V.; Kolesnikova, Julia S.; Yagudina, Elena V.; Kuznetsova, Alsu M.; Molchanova , Marina A. (Journal of Ecohumanism, 2024)
It has been established that the Russian Federation is one of the countries with a high level of corruption. Corruption has affected almost all levels of government. In 2023, its global anti-corruption ranking was very low, ranking 137th between Paraguay and Kyrgyzstan. This fact negatively affected the socio-economic development of modern Russia. The authors sought not only to reveal the reasons for its unprecedented growth over the past two decades, but also to show how corruption slows down the country's economic development, and why Russian anti-corruption policies do not produce real results. Based on factual material, the authors not only show the increase in the scale of corruption, point out significant shortcomings of anti-corruption policies and Russian legislation, but also identify the main ways to improve them for the purpose of further socio-economic development and improvement of public administration. There is a certain connection between the effectiveness of public management and corruption. This study can provide government authorities and management bodies of both Russia and other post-Soviet states, where the level of corruption is also high, with real assistance in improving the forms and methods of anti-corruption policy.